A Framework for Assessing Fiscal Sustainability and External Viability, with An Application to India - Parker, Karen (IMF Working Papers; Working Paper ;, 1993)
This paper presents a simple macroeconomic simulation model which can be used to evaluate alternative fiscal strategies and their implications for external viability. It attempts to bridge the gap between the literature on fiscal sustainability and the demands of operational work. The framework, developed in a spreadsheet format, generates estimates of public spending compatible with identified targets for growth, inflation and domestic and foreign borrowing. The difference between the spending path consistent with these targets and that based on current policies is the fiscal adjustment required to meet the authorities' macroeconomic objectives. Alternatively, the framework can be used to assess the implications for inflation, interest rates and public indebtendess of a given spending path. Finally, one can analyze the impact of financial reform on fiscal and external performance. The model is applied to India to illustrate the types of simulations that may be conducted.